2016
DOI: 10.1039/c6cp03563a
|View full text |Cite
|
Sign up to set email alerts
|

Interface-enhanced Li ion conduction in a LiBH4–SiO2 solid electrolyte

Abstract: We have developed a fast solid state Li ion conductor composed of LiBH4 and SiO2 by means of interface engineering. A composite of LiBH4-SiO2 was simply synthesized by high energy ball-milling, and two types of SiO2 (MCM-41 and fumed silica) having different specific surface areas were used to evaluate the effect of the LiBH4/SiO2 interface on the ionic conductivity enhancement. The ionic conductivity of the ball-milled LiBH4-MCM-41 and LiBH4-fumed silica mixture is as high as 10(-5) S cm(-1) and 10(-4) S cm(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 49 publications
(75 reference statements)
4
89
0
Order By: Relevance
“…30,36 Another approach is to increase the ionic conductivity of LiBH 4 by mixing it with oxides or by means of nanoconfinement. [37][38][39][40] As described above, halogenation represents a successful strategy to stabilize the LiBH 4 conducting phase at RT. However, the ionic conductivity alone is not sufficient for designing effective SEs, but it must be flanked by an elevate (electro)chemical compatibility between SE and electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…30,36 Another approach is to increase the ionic conductivity of LiBH 4 by mixing it with oxides or by means of nanoconfinement. [37][38][39][40] As described above, halogenation represents a successful strategy to stabilize the LiBH 4 conducting phase at RT. However, the ionic conductivity alone is not sufficient for designing effective SEs, but it must be flanked by an elevate (electro)chemical compatibility between SE and electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent interest in utilizing LiBH 4 as a solid-state electrolyte was established through the work of Orimo [4], who demonstrated that the ionic conductivity of lithium can be greater than 1 mS/cm at temperatures above the orthorhombic to hexagonal phase transition that occurs at 380 K [5]. This work has been expanded to achieve high conductivity in LiBH 4 based solid electrolytes through the addition of Li halide salts [6][7][8], nanoconfinement [9][10][11][12], nanoionic destabilization [13,14], ion substitution [15][16][17][18][19][20][21], and eutectic formation [22].…”
Section: Introductionmentioning
confidence: 99%
“…The narrow‐shaped 7 Li NMR (RT) spectrum of MCM41–LiBH 4 ‐91 resembled that of highly conductive hexagonal LiBH 4 . The fast Li + mobility in MCM41–LiBH 4 ‐91 may be mainly attributed to the interface interactions between nano‐LiBH 4 and SiO 2 , which was further proved by Choi et al They compared the ionic conductivities of the melt‐infiltrated porous‐LiBH 4 –MCM41 (MI‐LM) and ball‐milled‐LiBH 4 –fumed‐SiO 2 (BM‐LF) ( Figure a), and the ionic conductivity of the BM‐LF sample rivals that of MI‐LM, reaching 10 −4 S cm −1 . Note that two conspicuous differences exist between the MI‐LM and BM‐LF composites: i) the Brunauer–Emmett–Teller (BET) surface area for porous MCM‐41 (946 m 2 g −1 ) is about threefold that for nonporous fumed silica (362 m 2 g −1 ); and ii) LiBH 4 is nanoconfined in pure porous MCM‐41, but not in fumed silica.…”
Section: Progress Of Borohydride‐based Solid‐state Electrolytes and Amentioning
confidence: 73%
“…Interface Engineering Strategy (“Filler Effect”) : de Jongh and co‐workers studied the ionic conductivity of nanoconfined LiBH 4 in ordered mesoporous silica MCM‐41 scaffolds (4 nm pores) . MCM41–LiBH 4 ‐91 delivered an impressive ionic conductivity of 0.1 mS cm −1 at 313 K, which is 1000 times higher than for bulk LiBH 4 at the same temperature . In comparison with the activation energies of orthorhombic and hexagonal LiBH 4 (0.69 and 0.53 eV), that of the MCM41–LiBH 4 ‐91 composite was reduced to 0.43 eV, illustrating the smaller impact of temperature fluctuations on the ionic conductivity of MCM41–LiBH 4 ‐91.…”
Section: Progress Of Borohydride‐based Solid‐state Electrolytes and Amentioning
confidence: 99%
See 1 more Smart Citation